Forward Exchange Intervention: The British Experience, 1964-67 - Chalmers, Eric Brownlie (London : Hutchinson, 1971)
The volume brings together the contributions to a discussion of forward exchange intervention conducted in the Westminster Bank Review during 1966/67.
Includes bibliographical references.
rua 19/06/17
Loans.
Keywords: Foreign ExchangeFutures; Monetary Policy